Enhancing Arabic Vocabulary Acquisition through Interactive Multimedia: A Qualitative Study: Meningkatkan Pemerolehan Kosakata Arab melalui Multimedia Interaktif: Suatu Studi Kualitatif - Safitri, Iin Tyas; Ammar, Farikh Marzuki (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study explores the effectiveness of an interactive multimedia learning model for Arabic vocabulary acquisition. Conducted with Arabic teachers and students from a high school, the study utilized interviews, observation, and documentation for data collection. The interactive multimedia, comprising PowerPoint software and Android comic applications, was found to follow a three-stage process: planning, implementation, and evaluation. Positive factors driving multimedia adoption included existing manuals and engaging modifications of the software. Challenges included students' limited grasp of conversational Arabic and the placement of lessons. Addressing these, interactive learning media emerged as a solution to boost learning engagement. The study highlights the potential of interactive multimedia to enhance Arabic vocabulary learning, advocating for broader application in language education contexts. Highlights: Effective Learning Model: The study examines the efficacy of interactive multimedia in enhancing Arabic vocabulary acquisition among students. Three-Stage Process: The interactive multimedia learning model is structured into planning, implementation, and evaluation stages, providing a comprehensive framework. Enhancing Engagement: The research underscores the potential of interactive multimedia to address challenges in language learning, fostering student engagement and promoting effective vocabulary acquisition. Keywords: Arabic vocabulary, interactive multimedia, language acquisition, qualitative study, learning engagement.